Integrating arts with STEM and leading with STEAM to increase science learning with equity for emerging bilingual learners in the United States - Bradley S. Hughes; Michael W. Corrigan; Douglas Grove; Sage B. Andersen; Joseph T. Wong (SpringerOpen, 2022)
Abstract Background To inform STEM education for benefiting emerging bilingual (EB) and English fluent (EF) students, the present study evaluated the order effects of integrating science and arts within a large-scale, ongoing effort investigating the efficacies of Next Generation Science Standards (NGSS)-aligned Science Technology, Engineering, and Math (STEM) methodologies to provide more equitable opportunities to students to learn science through Arts integration (STEAM). The experiment examines the curriculum integrating order of implementing combinations of STEM and STEAM approaches in fifth grade life and physical science instruction, comparing (STEM → STEAM) vs (STEAM → STEM). Results T tests and a three-way between-groups analysis of covariance examined the impact of instructional order, language fluency, and teachers' implementation fidelity. Findings indicate similar results in life and physical sciences, in which the STEAM first approach produced significantly higher science learning gains for both EF and EB students, revealing some higher learning gains for EF students, but with greater STEAM first order effect advantages for EB students overall. While EF students show higher learning gain scores in the high fidelity classrooms, the advantage of the STEAM first order is greater for EB students in all classroom fidelity levels and even within low to moderate implementation fidelity classrooms, as may commonly occur, such that the integration order of STEAM before STEM strategy is particularly advantageous to EB learners. Conclusions The integration pattern of leading with STEAM and following with STEM offers an important opportunity to learn for EB students, and increases equity in opportunities to learn among EB and EF learners of science. Both EB and EF students benefit similarly and significantly in high fidelity implementation classrooms. However, the gains for EF students are not significant in low fidelity implementation classrooms, while in such low fidelity implementation classrooms, the EB students still benefited significantly despite the poor implementation. These results suggest that a strong compensating STEAM first order effect advantage is possibly involved in the implementation system for the EB population of learners. Teaching science through the arts with STEAM lessons is an effective approach that can be significantly improved through introducing STEM units with the STEAM first order effect advantage.